Pengaruh Strategi Crossword Puzzle Terhadap Hasil Belajar Siswa Kelas V SD Negeri 08 Rambang Kuang: Crossword Puzzle, Hasil Belajar, IPS Kelas Tinggi - Amalisa, Yeni; Idris, Muhamad; Suryani, Ida (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Strategy Crossword Puzzle (crossword puzzle) is a strategy that can activate a learning atmosphere where in the game the player must fill in the empty spaces (in the form of white boxes)with letters that form a word based on the instructions given. Usually, the instructions are divided into